WEAR BEHAVIOUR OF LOW ALLOY GREY CAST IRON (NF-GREY7): THE EFFECT OF FERROSILICON AND CARBONISED COCONUT SHELL NANOPARTICLE ADDITION - J. O. Agunsoye; S. A. Bello; A. K. Odunmosu (UNILAG Journal of Medicine, Science and Technology, 2019)
Effect of ferrosilicon and carbonised coconut shell nanoparticle additions on wear resistance of (NF-Grey 7) cast iron were studied. Alloys of (NF-Grey 7) cast iron were produced by a gradual increase in masses of the ferrosilicon and carbonised coconut shell nanoparticle additions using a green sand mould and stir cast technique. The behaviour of the material under shock energy impact and dry sliding wear conditions were studied. Results revealed that addition of the ferrosilicon and carbonised coconut shell nanoparticle additions to the (NG-Grey 7) cast iron enhanced the wear resistance and impact energy absorption more than what obtained in the earlier NG-Grey 7 cast iron reinforced with ferrosilicon and graphite micro particles. Hence, new alloy of cast iron for jaw crusher and other heavy equipment applications where wear resistance and energy absorption are a prime prerequisite has been developed.